Property Rights Reform to Support China’s Rural-Urban Integration : Village-Level Evidence from the Chengdu Experiment - Deininger, Klaus (Wiley, 2019)
As part of a national experiment, in 2008, Chengdu prefecture launched a series of property rights reforms, among them complete registration of all land and measures to ease transferability and eliminate labour market restrictions. A comparison of villages inside and outside the prefecture's border using a difference‐in‐difference approach suggests that the reforms have reduced administrative reallocations; aligned land use closer to economic incentives, mainly through market transfers; and stimulated enterprise startups. These results, most of which are more pronounced for villages closer to Chengdu city, illuminate the potential gains from factor market reform. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions. https://authorservices.wiley.com/author-resources/Journal-Authors/licensing/self-archiving.html